The application of law on pollution control towards marine biodiversity conservation in Malaysia - Mustafa, Maizatun; Ariffin, Mariani (2011)
The biodiversity of the world's oceans which constitutes more than 70 percent of the earth's surface is crucial for providing a broad and life-supporting range of ecosystem. Being a maritime nation, as well as one of the top biodiversity-rich countries in the world, it is important for Malaysia to give its full commitment in conserving her mega-diverse ecosystems, including that of the richly endowed seas. At present, the well being of Malaysia's marine biodiversity is facing increasing threat from various sources, notably that of land-based and vessel-based polution. Malaysia takes pollution issue seriously, and joins other key maritime nations in enhancing her legal regime in dealing with marine polluiton. This paper seeks to highlight Malaysia's continuous effort towards marine pollution control through the application of law. Significantly, such effort can be used as a reference by other maritime nations for the purpose of collective marine environmental protection and biodiversity conservation.